A dramatização do trágico em Yerma, bodas de sangre e la casa de Bernarda Alba, de Federico García Lorca - Rodrigues, Grygena dos Santos Targino (2018)
This thesis investigates the dramatization of the tragic in Bodas de Sangre, Yerma and La Casa de Bernarda Alba by Federico García Lorca, Spanish plays written in the first half of the twentieth century. In the first chapter, we analyze the historical-literary context related to the pieces, highlighting the conservative and patriarchal scenario of the Second Spanish Republic common to the trilogy. We also investigate the poetic theater produced by Federico, as well as the participation of the playwright in the group of the Generación del 27. In this chapter, we also reflect on the mythical and religious behavior of the rural culture of Andalusia, highlighting the atavistic sacredness and rustic Christianity of that population, in the light of the belated modernity of this culture. For this analysis, we consider definitions and reflections of several authors, such as Josephs and Juan Caballero (2012), Ian Gibson (2013), Ildefonso-Manuel Gil (2012), Mario González (2013), Maria Francisca Vilches de Frutos (2014), Ortega y Gasset (1944) and Castro Filho (2009). In the second chapter, we present an approach to drama theory from the basic foundations guiding dramatic art throughout the centuries. At first, we considered tragedy as an art form that seeks to frame the tragic in rationalist schemes and we approach the tragic as a philosophical and existential concept, linked to the finitude of life. In a second moment, we explore the pillars of modern drama, having as theoretical parameters concepts that can base critical reflections on the existence of tragedy in modern times, considering similarities and differences between classical and modern dramaturgy. For these discussions, we have contributions from Aristotle (1991b), Hegel (2010), Peter Szondi (2004, 2011), George Steiner (2006), Raymond Williams (2011), Terry Eagleton (2013), Sandra Luna (2012), among other authors. In the third chapter, we perform an analysis of the plays based on the theories examined in the previous chapters. In this perspective, we try to prove that the pieces in this trilogy are modern tragedies, for their emphasis on social dramas and the treatment of the subjectivities of the characters, who reveal interior dramas in opposition to the Andalusian social context of the 1930s. In addition to the parameters characteristic of modern drama, the pieces present conflicts which derive fatalistic traits from the use of taboos, religious dogmas, and rules of social conduct that interfere directly with the characters' individual conflicts. Added to this, it is worth mentioning the presence of a sacred and ritualistic dimension implied in the trilogy, which goes beyond the contextual realism of the plays and transcends the limits of reason, directly influencing the behavior and actions of the characters.